Effect of sprigging density and foliar nitrogen on the growth of Bermuda grass (Cynodon dactylon L. Pers. x Cynodon transvaalensis) - D Dhanasekaran (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2018)
Turf grasses have been utilized by humans to enhance their environment for more than 10 centuries. Aesthetically, lawns enhance the quality of life, contribute to social harmony and community pride, increase property values and compliment other landscape plants. The beauty of any garden largely depends on the greenness of the lawn. The first and foremost criteria for a well establishment and a satisfactory lawn are selection of suitable grass species and methods of its establishment. Hence, an experiment was laid out to study the effect of different sprigging density and foliar nitrogen on the growth and establishment of bermuda grass (Cynodon dactylon L. Pers. x Cynodon transvaalensis) in floriculture unit of the Department of Horticulture, Faculty of Agriculture, Annamalai University, Tamil Nadu during the year 2013-2015. Bermuda grass sprigs were planted in different spacing levels and foliar spray of urea with twelve treatment combinations comprising of different levels viz., 10 x 10 cm with 1%, 1.5% and 2%; 15 x 15 cm with 1%, 1.5% and 2%; 20 x 20 cm with 1%, 1.5% and 2%; 25 x 25 cm with 1%, 1.5% and 2%, in factorial randomized block design with three replications. From the results, it was found that the earliest spread and ground cover were observed in planting sprigs at closer spacing of 10 x 10 cm in combination with foliar application of nitrogen in the form of urea as 2 % for two times at seven and fifteen days after planting.